1977
DOI: 10.1113/jphysiol.1977.sp012022
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral circulatory and metabolic effects of 5‐hydroxytryptamine in anesthetized baboons.

Abstract: 1. The cerebral circulatory effects of the intracarotid administration of 5-hydroxytryptamine were examined in anaesthetized baboons. Cerebral blood flow was measured by the intracarotid 133Xe technique, cerebral O2 consumption and glucose uptake were measured as indices of brain metabolism and electrocortical activity was continuously monitored. 2. Despite a marked reduction in the calibre of the internal carotid artery (assessed angiographically), the intracarotid infusion of 5-hydroxytryptamine 0-1 microgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

1980
1980
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 27 publications
3
47
0
Order By: Relevance
“…In our previous studies relating to the effect of platelet products on the neurons of spinal explants, we had quantified by morphometric techniques the number and the size distribution of neurons in the ventral horns. We found, as reported by Delfs et al, 10 that >90% of the neurons in the ventral horns, both in the treated and control groups, were <500 fim 2 , and the major portion of this was in 100-200 /im 2 range. Although the number of neurons per ventral horn in the explants varied depending on the age of the animal, spinal level, and duration in culture before the experiment, these were strictly controlled for within each experiment.…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…In our previous studies relating to the effect of platelet products on the neurons of spinal explants, we had quantified by morphometric techniques the number and the size distribution of neurons in the ventral horns. We found, as reported by Delfs et al, 10 that >90% of the neurons in the ventral horns, both in the treated and control groups, were <500 fim 2 , and the major portion of this was in 100-200 /im 2 range. Although the number of neurons per ventral horn in the explants varied depending on the age of the animal, spinal level, and duration in culture before the experiment, these were strictly controlled for within each experiment.…”
Section: Methodssupporting
confidence: 70%
“…1 Among them, serotonin has been convincingly shown to suppress central nervous system function. 2 Arterial thrombi, a major cause of cerebral infarction, consist largely of platelets, constituting >50% by volume. This platelet concentration in thrombi amounts to 190 times the concentration in whole blood.…”
mentioning
confidence: 99%
“…Numerous studies have shown 5-HT to be a po tent cerebrovascular constrictor, both in vitro (Toda et aI., 1976;Forster and Whalley, 1982;Fu and Toda, 1983) and in situ (Edvinsson et aI., 1977). Although these studies examined large cerebral ar teries and pial arterioles, following circumvention of the blood-brain barrier, 5-HT administered sys temically produces reductions in CBF in the whole animal (Harper and MacKenzie, 1977;Grome and Harper, 1983), which would be consistent with there being a similar serotonergic constrictor influ ence upon the resistance vessels. More recently, pharmacological inhibition of endogenous 5-HT re lease, by systemic application of an agonist specific for the 5-HT1A autoreceptor, was found to induce increases in LCBF that were in excess of any con comitant changes in LCMRglc in the physiologically normal rat (McBean et aI., 1991).…”
Section: Discussionmentioning
confidence: 89%
“…There are several reports in vivo (17)(18)(19)(20) and in vitro (21)(22)(23)(24) that 5-HT caused a direct vasoconstriction and that this vaso constriction was attenuated by methysergide, so the experiments in reserpinized cats were carried out in order to further examine the effects of dopamine and serotonin on nigral induced decrease in striatal blood flow. It is well known that reserpine impairs the mechanism that stores catecholamines and serotonin, and it reduces the content of these active substances (25,26 by the serotonergic pathway from the raphe nucleus (39).…”
Section: Methodsmentioning
confidence: 99%